2005
DOI: 10.1093/bja/aei070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnesium sulphate and clonidine on propofol consumption, haemodynamics and postoperative recovery

Abstract: Clonidine caused bradycardia and hypotension and magnesium sulphate caused delayed recovery, but can be used as adjuvant agents with careful management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 17 publications
9
37
1
1
Order By: Relevance
“…Zalunardo MP et al Studied clonidine at a dose of 3 µg/kg noted that following Section: Anaesthesia laryngoscopy and intubation at 1 min HR increased by 23/min in control group and by only 6 /min in the clonidine pre-treated group and MAP rose by 37 mmHg in the control group and only 5 mmHg in the clonidine pre-treated group [6] . Altan A et al studied clonidine at a dose at 3 µg/kg noted that, following laryngoscopy and intubation, HR rose by 10 /min in the control group, whereas in the clonidine group, HR decreased by 10 /min, which is statistically highly significant (p<0.01) [7] . Ray M. et al Evaluated clonidine at a dose of 3 µg/kg noted that following laryngoscopy and intubation, HR at 1 min rose by 19 bpm in control group and only 1 bpm in clonidine group, the difference being statistically significant [8] .…”
Section: Discussionmentioning
confidence: 97%
“…Zalunardo MP et al Studied clonidine at a dose of 3 µg/kg noted that following Section: Anaesthesia laryngoscopy and intubation at 1 min HR increased by 23/min in control group and by only 6 /min in the clonidine pre-treated group and MAP rose by 37 mmHg in the control group and only 5 mmHg in the clonidine pre-treated group [6] . Altan A et al studied clonidine at a dose at 3 µg/kg noted that, following laryngoscopy and intubation, HR rose by 10 /min in the control group, whereas in the clonidine group, HR decreased by 10 /min, which is statistically highly significant (p<0.01) [7] . Ray M. et al Evaluated clonidine at a dose of 3 µg/kg noted that following laryngoscopy and intubation, HR at 1 min rose by 19 bpm in control group and only 1 bpm in clonidine group, the difference being statistically significant [8] .…”
Section: Discussionmentioning
confidence: 97%
“…Altan et al compared the eff ects of magnesium sulfate and clonidine on hemodynamic parameters during anesthesia and surgical procedure. MAP values recorded in patients receiving clonidine were significantly lower at all time intervals; however, the diff erence between the groups was not statistically significant 10 . Magnesium sulfate was used to prevent fl uctuation in arterial blood pressure during surgery for catecholamine-active glomus tumors in two patients.…”
Section: Discussionmentioning
confidence: 73%
“…Patients subjected to major surgical procedure without magnesium supplementation are exposed to an increased risk of hypomagnesemia during the early postoperative period 9 . Magnesium is also used as an eff ective antiarrhythmic agent 10 . Some in vitro studies demonstrated that magnesium prevented catecholamine release from the adrenal medulla and adrenergic terminals, and produced coronary vasodilatation 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Başka çalışmalarda da kullanılan magnezyumun dozları farklı olmakla beraber propofol tüketiminin azaldığı saptanmıştır. (2,(11)(12)(13) Magnezyumun inhalasyon anesteziği gereksinimini azaltır. (14,15) Buna karşılık, özel-likle sevofluran uygulamasının magnezyum ile etkileşimi konusunda intravenöz anestezikler ile karşılaştırıldığında çok daha az çalışma bulunmaktadır.…”
Section: Discussionunclassified